2011
DOI: 10.1242/jeb.057596
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopic fractionation in eider adipose tissue varies with fatty acid structure: implications for trophic studies

Abstract: SUMMARYCarbon isotopic fractionation was investigated in fatty acids (FA) of adipose tissue and blood serum of threatened Stellerʼs eiders (Polysticta stelleri) and spectacled eiders (Somateria fischeri) relative to the FA in their diets. Captive eiders were fed a known diet for 180 days with serum sampled at 60, 120 and 180 days immediately after a 12 h fast; adipose was collected at 180 days. Essential FA (EFA) in the adipose showed varying degrees of isotope fractionation (0-4‰), depending on FA structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 70 publications
2
40
0
Order By: Relevance
“…Such differences have mainly been attributed to FA-specific trophic fractionation of 13 C isotope that depends on the individual FA structure (Bec et al, 2011;Budge, Wang, Hollmen, & Wooller, 2011). However, we still found that in mesozooplankton δ 13 C values of essential FAs with 18C are significantly different from essential δ 13 C-EPA and δ 13 C-DHA values, while both EPA and DHA have similar δ 13 C values to bulk δ 13 C in POM.…”
Section: Mesozooplankton Metabolism and Dietary Sources According Tmentioning
confidence: 57%
“…Such differences have mainly been attributed to FA-specific trophic fractionation of 13 C isotope that depends on the individual FA structure (Bec et al, 2011;Budge, Wang, Hollmen, & Wooller, 2011). However, we still found that in mesozooplankton δ 13 C values of essential FAs with 18C are significantly different from essential δ 13 C-EPA and δ 13 C-DHA values, while both EPA and DHA have similar δ 13 C values to bulk δ 13 C in POM.…”
Section: Mesozooplankton Metabolism and Dietary Sources According Tmentioning
confidence: 57%
“…In a cultured diatom algae Thalassiosira pseudonana 20:5n-3 and 22:6n-3 were less enriched compared to 18:2n-6 and 18:1n-9 [41]. Budge et al [8] depicted the parabolic pattern for sea birds, eiders, fed on controlled diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, experimental tests are still rare and did not necessarily support this essential assumption [6][8]. Moreover, FA δ 13 C values of zooplankton and fish were not directly related to those of particulate organic matter in a marine field study [4].…”
Section: Introductionmentioning
confidence: 99%
“…The FA-specific stable isotope composition of carbon was measured in FAME derivatives of the diatom-associated FAs 16:1n-7 and 20:5n-3, and the dinoflagellate-associated FAs 18:4n-3 and 22:6n-3 in POM and krill (CSIA; Kohlbach et al, 2016). During transesterification, a methyl group is added to the FA, which can result in a difference in δ 13 C values between the free FA and the corresponding FAME (e.g., Budge et al, 2011). In a preparatory experiment for this study, however, we did not find significant differences between the δ 13 C values of the free FA and the FAME (e.g., 16:0 FA: −28.56 ± 0.12‰, 16:0 FAME: −28.57 FIGURE 1 | Map of the sampling area during "Polarstern" expedition PS81 in the Weddell-Scotia Confluence Zone (14 August to 16 October 2013) with sea ice concentration (Spreen et al, 2008).…”
Section: Bulk and Compound-specific Stable Isotope Analysesmentioning
confidence: 99%
“…The mixing models can account for different isotopic turnover rates in the consumers. However, krillspecific trophic enrichment of 13 C is unknown, and was thus assumed to be zero for both BSIA and CSIA models (Budge et al, 2011;Graham et al, 2014;Wang et al, 2015). For the BSIA models, trophic enrichment of 15 N was assumed to be 3.4‰ per trophic level (Minagawa and Wada, 1984).…”
Section: Quantification Of Ice Algal Carbonmentioning
confidence: 99%